Phytochemical Profiling, and Antifungal Potentials of Stem-Bark Extracts of East African (Khaya Anthotheca) - Umaru, Kerenhappuch Isaac; Ugoeze, Egeonu Stephen; Umaru, Isaac John; Nanmar, Chakfa; Tansaba, Akafa Andes; David, Bando Christopher (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Fungal infection is an infectious disease that is commonly implicated as aetiologic agents that contribute to the increasing burden of morbidity and mortality in developing countries as a result misdiagnosis or improper diagnosis. This study determined the profiling and antifungal potentials of Stem-Bark Extracts of East African (Khaya Anthotheca). The methanol solvent was used for disc diffusion assay. The inhibitory concentration of the extract was performed by broth dilution method and zone of inhibition was studied by disc diffusion method at the concentration of 50, 100, 250, and 500 in DMSO. Nystatin was used as the reference control for antifungal study. The extract showed maximum inhibition potential sof zone of inhibition against most of the pathogen (Aspergillus niger, Aspergillus flavus, Candida tropicalis and Fusarium oxysporium) used at concentration 50ppm to 500ppm. The zone of inhibition for 500ppm is shown as (319.12± 0.11, 19.23 ± 0.12, 20.33±0.23* and 18.34±0.21*mm respectively). The extract showed minimum inhibition potential against Aspergillus flavus in all the concentration when compared with the control as well as to the other pathogens. Candida tropicalis and Fusarium oxysporium was found to be more sensitive to the methanol extract followed by Aspergillus flavus and Aspergillus niger lastly. The extract was found to be rich in phytochemical, with about 20 different chemical constitutes, with 12.14- Pentane, 3-ethyl-2,4-dimethyl-, 14.66-3-Hexen-2-one and 27.23-2-Nonenal, 2-pentyl-as the highest. The Present study indicates the potential usefulness of methanol extract of extract of khaya anthotheca as antifungal agent. Thus, has therefore, contributed to the pool of knowledge already available in this area of research. Considering the effects that both phytochemicals and its potentials as antifungal, it would be expedient to conduct further studies to assess its cancer potentials.